Truck attack: Fear of ISIS and reminder of truck attacks in Europe as associated with psychological distress and PTSD symptoms. (September 2018) - Mahat-Shamir, Michal; Hoffman, Yaakov; Pitcho-Prelorentzos, Shani; Hamama-Raz, Yaira; Lavenda, Osnat; Ring, Lia; Halevi, Uzia; Ellenberg, Eytan; Ostfeld, Ishay; Ben-Ezra, Menachem
Highlights: Association between stress disorders and vulnerability variables. Association between physical proximity to an ISIS attack and stress disorders. Association between ISIS anxiety & Danger perception and stress disorders. Stress disorders were not associated with association via location. Association by recency & similarity were associated only with psychological distress. Abstract: Following an ISIS attack, the present study examined the association between psychological distress and severe stress symptoms with vulnerability variables: i.e. Physical proximity to the site of the terror attack, Associative memory of prior events, Danger perception and ISIS anxiety. Using an online survey, 397 adult participants were recruited, Seventy-two hours after an ISIS terror attack, and filled out Psychological distress Patient Health Questionnaire 4 and severe stress symptoms questionnaire as well as physical proximity to the site of the terror attack, associative memory of prior events, danger perception and ISIS anxiety scales. Physical proximity to the site of the terror attack and ISIS anxiety were found to be significantly associated of both psychological distress and severe stress symptoms. Regarding danger perception, only danger perception of terror attacks was associated with both psychological distress and with severe stress symptoms. Lastly, whereas being reminded of the 2014 Jerusalem tractor attack (tapping to association via location) was neither associated with psychological distress nor with severe stress symptom, the reminder of the truck attack in Berlin (tapping into association by recency and similarity) was associated with psychological distress but not with severe stress symptoms. The importance of the findings is discussed.